Extraction and partial characterization of a coagulant preparation from Silybum marianum flowers: its action on bovine caseinate - Vairo Cavalli, Sandra Elizabeth (2005)
An outstanding parameter in cheese making is the type of coagulant, which greatly influences the characteristics of the final products. Proteolysis is the most important set of biochemical changes during ripening of most cheeses, and is carried out, in different magnitude, by proteolytic agents originated in milk, rennet (or rennet substitute), and starter and non-starter micro-organisms (Silva & Malcata, 2000). The demand for alternative sources of milk coagulants, to replace the expensive and limited natural rennet supplies, has increased (Esteves et al. 2001). All commercial enzymes employed as milk coagulant are aspartic proteinases, which are most active at acidic pH and preferentially cleave peptide bonds between residues with hydrophobic side-chains (Silva & Malcata, 1999). Because of the presence of aspartic proteinases, aqueous crude extracts from flowers of Cynara cardunculus (Verı´ssimo et al. 1995, 1996), Cynara humilis, and/or Cynara scolymus are traditionally employed in the Iberian Peninsula as vegetable rennet for cheesemaking (Reis et al. 2000). Milk clotting activity was also proved in flowers of Centaurea calcitrapa and Onopordum turcicum (Tamer, 1993; Domingos et al. 1998). All these species are included within the Asteraceae family and furthermore in the same tribe : Cardueae Cass.=Cynareae Less. (Ariza Espinar & Delucchi, 1998). When a potential rennet substitute is studied, it is particularly important to evaluate adequately the degradation patterns of the caseins because of their effects on yield, consistency, and flavour of the final cheese (Fox, 1989). It is important to guarantee a well-balanced breakdown of curd proteins (caseins) in order to avoid formation of undesired attributes in cheese such as low viscosity and high bitterness (Visser, 1993). One of the most frequently used methods to monitor proteolytic processes on caseins is urea-polyacrylamide gel electrophoresis. On the other hand, tricine-SDS polyacrylamide gel electrophoresis improves the separation, identification and quantification of casein hydrolysates because it allows the visualization of large and small peptides (Pardo & Natalucci, 2001), with the additional advantage of allowing the estimation of molecular masses. Both methods are then suitable to characterize the performance of vegetable rennet in different ways. This preliminary study had the following objectives: the partial characterization of (i) the aspartic proteolytic activity present in flowers of Silybum marianum (L.) Gaertn. (Asteraceae); and (ii) the hydrolytic profile of bovine caseins.